Cloud Computing in Bangladeshi Higher Educational Institutions: Influential Factors and Adoption Model - Rahman, Mohammad M.; Rahman, Muhammad A. (AIUB Journal of Business and Economics, 2019)
In recent years, Cloud Computing (CC) is as one of the most relevant and significant research trends in Information technology (IT). This paper aims to identify the factors, benefits, and challenges while adopting CC in Higher Educational Institutions (HEIs) in Bangladesh. Many HEIs are shifting from traditional IT services to Clouds because it makes the academic process more efficient and effective. Cloud Computing offers huge benefits to HEIs such as boosts collaborative research activities, storage and backs up data, improves filling and 24/7 accessible facilities from remote locations, provides latest software and applications for financial and HR management, online learning management system, improves accountability and various services with minimum start-up cost. Besides the utmost benefits it offers for the HEIs, increasing financial pressure forces them to consider adopting CC because it reduces cost and pay-per-use pricing model. Globally researchers are showing interest in the adoption of CC in HEIs sector, but factors are still unexplored for Bangladeshi HEIs context. As a result, to fill this gap is required to identify influential factors, benefits and what challenges Bangladeshi HEIs face while adopting CC. Therefore, TAM and TOE theory is used to develop a conceptual model to identify influential factors for Bangladeshi HEIs.